2013
DOI: 10.1111/obes.12052
|View full text |Cite
|
Sign up to set email alerts
|

Fitting and Forecasting Sovereign Defaults using Multiple Risk Signals

Abstract: In this article, we try to realize the best compromise between in-sample goodness of fit and out-of-sample predictability of sovereign defaults. To do this, we use a new regressiontree based approach that signals impending sovereign debt crises whenever pre-selected indicators exceed specific thresholds. Using data from emerging markets and Greece, Ireland, Portugal and Spain (GIPS) over the period 1975-2010, we show that our model significantly outperforms existing competing approaches (logit, stepwise logit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 49 publications
(46 reference statements)
4
48
1
Order By: Relevance
“…Reduction of debt service fees and short-term debt is considered as the main challenge for developing countries (Roubini, 2001). Considering these notions, the following predictor variables for probability models were identified that are based on closely related previous contributions-Roubini (2001); Manasse and Roubini (2009) ;Fuertes, and Kalotychou (2007); Jorra (2012); Manasse et al (2003); Schaltegger et al (2015); Savona and Vezzoli (2015) : macro-indicators: real economic growth ( ) g d , real exchange rates ( ) e d , the US Fed Fund rate (ι ) Fed taken from US Federal Reserve website; insolvency: trade openness defined as real exportsþimports over real GDP ( ) tro d and technical efficiencies-θ θ θ θ ( * ) :…”
Section: Data and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of debt service fees and short-term debt is considered as the main challenge for developing countries (Roubini, 2001). Considering these notions, the following predictor variables for probability models were identified that are based on closely related previous contributions-Roubini (2001); Manasse and Roubini (2009) ;Fuertes, and Kalotychou (2007); Jorra (2012); Manasse et al (2003); Schaltegger et al (2015); Savona and Vezzoli (2015) : macro-indicators: real economic growth ( ) g d , real exchange rates ( ) e d , the US Fed Fund rate (ι ) Fed taken from US Federal Reserve website; insolvency: trade openness defined as real exportsþimports over real GDP ( ) tro d and technical efficiencies-θ θ θ θ ( * ) :…”
Section: Data and Measurementsmentioning
confidence: 99%
“…The dependent variable is binary: takes value of 1 if country is defaulted and 0 otherwise. The data on external debt and crises were composed from the following sources: Manasse et al (2003); Manasse and Roubini (2009);Schaltegger et al (2015); Sturzenegger et al (2007) and Savona and Vezzoli (2015). Based on above mentioned studies and Moody's report, we identify the actual default and crises cases on their external debt obligations.…”
Section: Data and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is understandable as the attention of the financial world, the academic community, and the general public has been devoted to sovereign defaults (e.g. Cuadra and Sapriza, 2008;Eichler, 2014;Kohlscheen, 2010;Manasse et al, 2003;Saiegh, 2005;Savona and Vezzoli, 2015;Van Rijckeghem and Weder, 2009;Yue, 2010), which have been far more prevalent in the developing world. Until the Greek debt crisis in 2012, advanced economies in the post-WWII period simply did not default.…”
Section: Consolidated Democracy Advantage: Political Instability and mentioning
confidence: 99%
“…All our models, therefore, also control for the economic factors that are known to be related to government bond spreads: GDP growth, inflation, domestic short-term interest rate, fiscal deficit, public debt, international reserves, and EMU membership. GDP growth rate represents short-term business cycle fluctuations, with better performance generally reducing country risk premium and thus dampening the government bond spread (Savona and Vezzoli, 2015). Inflation is the change in overall price level and is often used in empirical studies as a proxy for macroeconomic stability.…”
Section: Data and Estimationmentioning
confidence: 99%